Cephalometric assessment of soft tissue morphology of patients with acromegaly - Bavbek Nehir Canigur; Tuncer Burcu Balos; Tuncer Cumhur; Gungor Kahraman; Ozkan Cigdem; Arslan Emre; Altinova Alev Eroglu; Akturk Mujde; Toruner Fusun Balos (Sciendo, 2016)
To assess the sagittal soft tissue morphology of patients with acromegaly in comparison with a healthy control group.